The Image of Immigrants as Anarchists in the American Press, 1886-1888 - Wasilewski, Krzysztof (Hungarian Journal of English and American Studies, 2020)
The article analyzes the American press coverage of anarchism and anarchists between 1886 and 1888. The bomb explosion during the May 4, 1886, mass protest in Chicago started a wave of “anarchism scare” that swept through the United States. Anarchism and anarchists became one of the major public topics of the period. Relying on theoretical concepts such as libertarian press theory and René Girard’s idea of the scapegoat, and applying the method of critical discourse analysis, I explore how local and metropolitan US newspapers framed anarchism as a foreign ideology professed only by immigrants, making them the collective scapegoat for the social upheaval. The press set the standard of “appropriate behavior,” according to which all patriotic and loyal citizens were to accept the political and economic system and those who thought otherwise were branded anarchists and foreigners. Therefore, the American press proved to be an important pillar of the sociopolitical system. (KW)